EDUCATING CHILDREN ON LEGAL MATTERS THROUGH LOCAL WISDOM PRINCIPLES APPROACHES AND ENHANCING RESTORATIVE JUSTICE IN THE CRIMINAL LAW SYSTEM - Suwito Suwito; Jonneri Bukit; Ade Sathya Sanathana Ishwara; Hardi Done; Isabel Moodley (Universitas Internasional Batam, 2023)
Providing a safe environment for children with legal issues is crucial in order to reduce the likelihood that they may commit similar crimes in the future. However, modern methods are often punitive and overlook the need of victim counselling and rehabilitation. This research seeks to address (1) How might a restorative approach be included into the resolution of juvenile court cases? and (2) How to tap into indigenous knowledge to implement Restorative Justice practices that help young offenders in Indonesia. The normative judicial procedure is adopted for this study. The findings highlighted the necessity to reevaluate the priority of customary law in attaining Restorative Justice in resolving legal disputes involving children in Indonesia. From the perspective of adat and local knowledge, criminal cases are issues that can only be handled with the participation of victims, their families, and the surrounding community. When it comes to investigating crimes, indigenous methods and local knowledge take cultural and social factors into account as well. The offered penalty is punitive, edifying, and beneficial to society as a whole in this circumstance. When put into practice, this method may enhance the restorative justice system in criminal law and educate youngsters how to cope with legal issues